The role of infant nutrition in the prevention of future disease - Ron eShaoul; Ron eShaoul; Yigal eElenberg; Yigal eElenberg; Yigal eElenberg (Frontiers Media S.A., 2014)
There is growing evidence that nutrition is part of the environmental factors affecting the incidence of various diseases. The effect starts in the prenatal life and affects fetal growth and continues in early life and throughout childhood. The effect has been shown on various disease states such as allergic diseases, hyperlipidemia and cardiovascular diseases, obesity, type II diabetes and metabolic syndrome and immunologic diseases such as celiac disease and type 1 diabetes mellitus. It seems that the recommendations of exclusive breastfeeding until the age of 4 months and subsequently exposure to various solid foods has beneficial effect in terms of allergic, immune and cardiovascular diseases prevention. Will these recommendations change the natural course of these diseases is unknown yet, but there is an accumulating evidence that indeed this is the case. In this review we review the evidence of early nutritional intervention and future disease prevention.